PENGARUH INDEKS PEMBANGUNAN MANUSIA, PERTUMBUHAN EKONOMI, DAN BELANJA OPERASIONAL TERHADAP JUMLAH ALOKASI BELANJA MODAL PADA PEMERINTAHAN KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - ANDAIYANI, ANDAIYANI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This study with respect to the indekx of human development, economic growth and operating expenditure to total capital expenditure in the province of West Kalimantan. The method used to determine the effect of these is the method of associative or causal design. Associative or causal design method is useful for analyzing research relationships between one variable with another variable or how one variable affects the other variable. The population in this research is all the District / City of West Kalimantan province consisting of 12 districts and 2 cities. The samples are part of the population, from this statement that the samples taken in this study at 100%, so the sample size is a total of 14 districts / cities in West Kalimantan Province. This research uses panel data which combines time series data (for 4 years, ie 2007 to 2010) and the cross section data for districts / cities in 12, thus forming the observed amount of data as much as 48 data (12 districts / cities over a period of 4 years). In this research, quantitative analysis is used in order to test and analyze whether there is an influence of human development, economic growth, and operating expenditure to total capital expenditure at the district / city in the province of West Kalimantan using Multiple Linear Regression analysis tool. The result is a variable significant human development index (significantly) the amount of capital expenditure, economic growth is not a significant variable for the amount of capital expenditure, operational expenditure variable is not significant to the amount of capital expenditure. Keywords : human development, economic growth, operational expenditure, capital expenditure